Use of steel slag as sustainable construction materials: A review of accelerated carbonation treatment - Song, Qifeng; Guo, Ming-Zhi; Wang, Lei; Ling, Tung-Chai (Resources, conservation and recycling, 2021)
•Chemical compositions and utilization of steel slag were reviewed.•Principles of accelerated carbonation of steel slag were elucidated.•Effects of various factors on accelerated carbonation of steel slag were detailed.•Applications of carbonated steel slag as construction materials were introduced. Steel slag is a by-product discharged from the steelmaking process, which is characterized by abundant free calcium/magnesium oxide, low cementitious properties, and high contents of heavy metals. The disposal of steel slag at landfills not only wastes valuable resources but also causes serious pollutions to the environment. However, the direct use of untreated steel slag poses a great risk to the mechanical properties and durability of the steel slag-derived composites. In recent years, research on the use of steel slag as eco-friendly construction materials has experienced an unprecedented advance, particularly with the discovery that accelerated carbonation is conducive to improving the inferior properties. This review summarizes the various types of steel slags based on chemical/mineral compositions and the related physic-chemical properties. It also highlights recent progress on the use of accelerated carbonation to improve the quality of steel slag in the context of a wide range of influencing factors, such as temperature, reaction time, CO2 concentration and pressure, moisture, particle size and gradation of steel slag, and additives. A major challenge is to dissect the interconnectedness between the influencing factors and their relative contributions to the property improvement of steel slag. After that, we introduce the practical applications of carbonated steel slag with improved properties. Finally, we provide new insights into the mechanisms and challenges of using accelerated carbonation as a treatment of steel slag for future research and industrial applications. [Display omitted]